Postcolonial Critique of Agrarian Law and Land Inequality in Indonesia - Suprapto Suprapto (The Indonesian Journal of Critical Legal Studies, 2026)
Land inequality remains a persistent sociolegal issue in Indonesia despite decades of agrarian reform initiatives and legal reforms aimed at promoting equitable access to land resources. This study offers a postcolonial critique of Indonesia’s agrarian law by examining how historical legacies of colonial governance continue to influence contemporary land relations and patterns of inequality. Employing a Critical Legal Studies and postcolonial theoretical framework, the research analyzes the development of agrarian regulations, land administration systems, and property rights structures. The findings indicate that many contemporary legal arrangements retain institutional characteristics rooted in colonial land governance, including centralized authority, commodification of land, and unequal recognition of customary land rights. These legal structures contribute to the concentration of land ownership and the marginalization of rural and indigenous communities. The study further reveals that legal discourse often presents land regulation as neutral and objective while obscuring underlying power relations that shape access to resources. From a postcolonial perspective, agrarian law reflects broader historical processes of domination and exclusion that continue to affect social and economic development. The research argues that addressing land inequality requires reexamining the ideological assumptions embedded within existing legal frameworks and promoting more inclusive approaches to land governance. Greater recognition of customary tenure systems and participatory decision-making processes may contribute to more equitable outcomes. The study concludes that agrarian reform should involve not only legal redistribution measures but also critical reflection on the historical foundations of contemporary land law. These findings enrich critical legal scholarship concerning law, colonial legacies, and social justice in Indonesia.